2014
DOI: 10.3310/hsdr02110
|View full text |Cite
|
Sign up to set email alerts
|

Mobilising identities: the shape and reality of middle and junior managers’ working lives – a qualitative study

Abstract: BackgroundSocial identities shape how individuals perceive their roles and perform their work. Yet little is known about the identities of various types of NHS managers and even less about how they may influence how they carry out their work to achieve effectiveness.ObjectivesTo chart the work of middle and junior clinical and non-clinical managers; to describe how their identities are constructed and shape the performance of their roles; to explore how they mobilise their identities to achieve effectiveness.D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…Managers in all settings reported that they often felt limited in their power to discipline or control clinical staffespecially senior physicians. In part, this was because of lack of leadership capacity, but it was also linked to the dependence of managers on the cooperation of those they seek to manage (Harvey et al 2014). In the African hospitals, managerial willingness to take unpopular action against highly-qualified staff was further undermined by the ability of such staff to move elsewhere given skill shortages nationally.…”
Section: Don't Think Anybody Has the Right To Penalise Us [Senior mentioning
confidence: 99%
“…Managers in all settings reported that they often felt limited in their power to discipline or control clinical staffespecially senior physicians. In part, this was because of lack of leadership capacity, but it was also linked to the dependence of managers on the cooperation of those they seek to manage (Harvey et al 2014). In the African hospitals, managerial willingness to take unpopular action against highly-qualified staff was further undermined by the ability of such staff to move elsewhere given skill shortages nationally.…”
Section: Don't Think Anybody Has the Right To Penalise Us [Senior mentioning
confidence: 99%
“…Managers in all settings reported that they often felt limited in their power to discipline or control clinical staff -especially senior physicians. In part, this was because of lack of leadership capacity, but it was also linked to the dependence of managers on the cooperation of those they seek to manage (Harvey, et al, 2014). In the African hospitals, managerial willingness to take unpopular action against highly-qualified staff was further undermined by the ability of such staff to move elsewhere given skill shortages nationally.…”
Section: At the Moment There Is No Follow Up … So I Can Create An Actmentioning
confidence: 99%
“…Although earlier studies (DeCampli et al., 2010; Saifman & Sherman, 2019) point out that nurse managers are important for organisational development, the nurse managers in this study were pressured from both their superiors and their employees. Nurse managers struggle with their identity and support is needed to strengthen that identity (Harvey et al., 2014). Support from superior managers is essential if a nurse manger is to continue working (Adriaenssens et al., 2017; Skytt et al., 2007; Titzer et al., 2013).…”
Section: Discussionmentioning
confidence: 99%